Antiviral Activity of Composition of Sulfur and Iodine Nanoparticles - Derevianko, S.V.; Vasylchenko, A.V.; Kaplunenko, V.H.; Kharchuk, M.S.; Demchenko, O.A.; Zhylikhovska, T.V.; Pavliuk, T.V.; Дерев'янко, С.В.; Васильченко, А.В.; Каплуненко, В.Г.; Харчук, М.С.; Демченко, О.А.; et al. (PH "Akademperiodyka" of the NAS of Ukraine, 2025)
The search for new antiviral substances is of great scientific and practical importance. One of the industries requiring the development and implementation of new antiviral and disinfectant agents is agriculture. Advances in nanotechnology open up broad prospects for the production and use of non-metal nanoparticles (NPs) for the development of antiviral drugs. The study aimed to examine the activity of S and I NP compositions against the porcine enterovirus encephalomyelitis virus Teschovirus A (PTV-1) and potato acropetal necrosis virus Y (PVY). Methods. The antiviral activity of the S and I NP compositions against Teschovirus A was determined in a pig embryo kidney cell culture. The virus titer in the control and study variants was calculated using the Reed and Mench method. The antiviral activity of the S and I NP composition against PVY was determined on indicator plants. The infection presence in indicator plants was determined by visual observation and serological methods. The interaction between NP and viruses was studied using transmission electron microscopy (TEM). Results. According to the virucidal studies, S and I NP composition exhibits high antiviral activity against the PTV-1 Dniprovskyi 34 strain, reducing the virus titer by 5.0 lg TCD50/cm3, and has a chemotherapeutic index of 8. The TEM analysis established that the S and I NPcomposition leads to PTV-1 morphology changes and does not exhibit antiviral activity against the PVY virus. The potential mechanism of the S and I NP composition’s antiviral activity against the PTV-1 Dniprovskyi 34 virus strain may lie in the direct binding of NPs to the viral surface. Adsorbed NPs are transformed into active forms, damaging capsid proteins. The resistance of PVY to the S and I NP composition is due to the fact that viral capsids do not contain areas enriched with NH-, SH-, and phenolic groups on the surface vulnerable to active forms of S and I. Conclusions. The S and I NP composition can be recommended for the creation of antiviral drugs and disinfectants against teschoviruses.